The relationship between body appreciation and weight-related health behaviors among Chinese adolescents - Zhong, Yuyuan; Chen, Ying; Wang, Meng; Lu, Bian; Shen, Ting; Hu, Jing; Jiang, Fengyang; Wang, Hongmei (Frontiers in Psychology, 2025)
IntroductionResearch on body appreciation has flourished globally in recent years. College students and adults, rather than adolescents have been mainly focused in China. Therefore, this study aims to investigate the current status of body appreciation and weight-related health behaviors among Chinese adolescents, and elucidate their multifaceted relationships.MethodsA total of 487 students from two junior high schools were selected through stratified cluster sampling for this cross-sectional study conducted in Hangzhou city, China. Data were collected by using the questionnaire including the Body Appreciation Scale-2 (BAS-2), the Physical Activity Questionnaire for Adolescents (PAQ-A), and the self-designed Food Frequency Questions.ResultsThe study showed current status of body appreciation among Chinese adolescents, with a majority categorized as physically inactive and having unhealthy dietary behaviors, leading to abnormal weight. Notably, this study provided novel evidence linking body appreciation with positive weight-related behavioral outcomes in both physical activity and dietary behaviors (such as sufficient fruit and vegetable consumption and reduced fried food intake) among Chinese adolescents. Besides, this study also revealed the impact of gender, mother's education, and household income on weight-related health behaviors among adolescents.DiscussionThis study emphasized the significant relationships between body appreciation and weight-related health behaviors among Chinese adolescents. These findings present empirical evidence for the development of intervention programs aimed at fostering body appreciation and promoting weight-related health behaviors in adolescents.